CYTOMEGALOVIRUS INFECTION IN A CHILD WITH SPINAL AMYOTROPHY - L. B. Kisteneva; A. K. Shakaryan; I. V. Mitrofanova; I. Y. Leontyeva; S. V. Shachgildyan; N. A. Malishev (LLC "Diagnostics and Vaccines", 2015)
This article describes a clinical case, representing the diagnostic difficulties. The baby of 4 months with bright neurological symptoms that appeared after vaccination, and coming with a diagnosis of "post-vaccination complications" in the survey diagnosed active cytomegalovirus infection and spinal muscular atrophy type 1. The role of the infective matter within the underlying disease was analyzed.